A rubber hose for oil mining
By adding scale filler and aerogel nanoparticles to the rubber hose to form a protective structure and enhance the connection, the problem of rubber hose aging in harsh environments is solved, and the corrosion resistance and wear resistance are significantly improved, and the service life is extended.
Patent Information
- Application Number
- CN202410642780.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-23
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-05-23
AI Technical Summary
Existing rubber hoses are prone to aging in harsh oil mining environments, and the effect of anti-aging agents is weakened after surface damage, making it difficult to effectively improve their aging resistance and service life.
Add scale filler and aerogel nanoparticles to the rubber hose. The scale filler forms a layered protective structure. The aerogel nanoparticles enhance the connection strength and adsorb corrosive substances. The nanoparticles are improved through ultrasonic treatment and graft modification treatment. .
It significantly improves the corrosion and wear resistance of rubber hoses, extends service life, and reduces expansion and wear rates in high temperature and high oil environments.
Smart Images

Figure BDA0004853825620000081 
Figure BDA0004853825620000091 
Figure BDA0004853825620000092
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of new materials, in particular to a rubber hose for petroleum mining. Background Art
[0002] Rubber hoses are widely used in oil extraction, but oil extraction is generally in a very harsh environment. Rubber hoses need to face a natural environment with high salt, high corrosion, and high oil pollution. Long-term exposure to such a harsh environment can easily lead to aging of the rubber hoses. In particular, oil pollution, corrosive aqueous solution systems, etc. will corrode and swell the rubber hoses, thereby destroying the stability of the molecular structure in the rubber hoses and causing undetectable defects.
[0003] In the prior art, anti-aging agents are generally added to rubber hoses to enhance the anti-aging properties of the rubber hoses and prevent the rubber hoses from aging or damage due to harsh environments. However, this anti-aging strategy has certain limitations. In particular, when the surface of the rubber hose is physically damaged by factors such as mechanical wear or aging factors, the anti-aging effect of the anti-aging agent will gradually weaken. This is because the inner layer material of the rubber hose will be exposed to external corrosive substances or conditions at a higher frequency and larger surface after surface aging, resulting in accelerated aging.
[0004] In view of this, how to improve the aging resistance of rubber hoses and increase the service life of rubber hoses has become one of the technical problems that need to be solved urgently. Summary of the invention
[0005] In view of this, the present invention proposes a rubber hose for petroleum mining and a preparation method thereof, aiming to improve the aging resistance by optimizing the raw materials thereof.
[0006] The technical solution of the present invention is implemented as follows: the present invention provides a rubber hose for petroleum mining, the raw materials of the rubber hose are calculated by weight and include: 80-90 parts of base rubber, 10-15 parts of flake filler, 0.1-1 part of aerogel nanoparticles and 1-5 parts of additives, the average particle size of the flake filler is 100-1000μm, and the average particle size of the aerogel nanoparticles is 50-100nm.
[0007] In some embodiments, the flake filler is flake graphite.
[0008] In some embodiments, the aerogel nanoparticles are carbon aerogel nanoparticles.
[0009] In some embodiments, the surface of the aerogel nanoparticles is subjected to a grafting modification treatment with terminal hydroxyl nitrile rubber, and the modification method comprises: dissolving the terminal hydroxyl nitrile rubber in toluene to obtain an active solution, adding the aerogel nanoparticles to the active solution, ultrasonically treating for 30-60 minutes, filtering and drying to obtain grafted modified aerogel nanoparticles.
[0010] In some embodiments, the mass concentration of the hydroxy-terminated nitrile rubber in the active solution is 5-10%.
[0011] In some embodiments, the base rubber is one of nitrile rubber, styrene butadiene rubber, chloroprene rubber, and fluororubber.
[0012] In some embodiments, the auxiliary agent includes: a filler, a vulcanizing agent and an anti-aging agent.
[0013] In a second aspect, the present invention further provides a method for preparing the above-mentioned rubber hose for oil mining, comprising the following steps:
[0014] Step 1: firstly, mixing and dispersing the flake filler and the aerogel nanoparticles to obtain a first mixture;
[0015] Step 2: Mix the remaining raw materials with the first mixture and add them into a mixer for mixing, and extrude the mixed materials through an extruder to obtain a rubber hose;
[0016] Step 3: vulcanize the rubber hose to obtain a rubber hose.
[0017] In some embodiments, before the flake filler is mixed with the aerogel particles, the method for preparing the carbon aerogel nanoparticles includes:
[0018] Resorcinol and formaldehyde are mixed, sodium carbonate is used as a catalyst, and the mixture is stirred in deionized water for reaction. The mixture is then subjected to heat aging treatment to obtain a hydrogel. The solvent is replaced with ethanol, and then the solvent is removed by drying. The mixture is then subjected to high-temperature carbonization treatment under nitrogen protection to obtain a carbon aerogel. The carbon aerogel is crushed to obtain carbon aerogel nanoparticles.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] The present invention adds flake fillers and aerogel nanoparticles to the raw materials of the rubber hose, wherein the added flake fillers form a stacked layered protective structure in the rubber hose, effectively reducing the speed and amount of external corrosive substances entering the inner side of the rubber hose, thereby improving the corrosion resistance of the rubber hose. At the same time, the added aerogel nanoparticles can be filled between the layers of the flake fillers, and the connection strength between the flake fillers can be enhanced through the bridging effect of the aerogel nanoparticles, thereby improving the wear resistance of the rubber hose. In addition, the aerogel nanoparticles can also adsorb and block corrosive substances entering the rubber hose body from the outside. DETAILED DESCRIPTION
[0021] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0022] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those of ordinary skill in the art to which the embodiments of the present invention belong. If the definitions set forth in this section are contrary to or otherwise inconsistent with the definitions set forth in the patents, patent applications, published patent applications, and other publications incorporated herein by reference, the definitions listed in this section take precedence over the definitions incorporated herein by reference.
[0023] Unless otherwise specified, the methods used in the following examples are all conventional methods. Unless otherwise specified, the materials, reagents and instruments used are all conventional materials, reagents and instruments in the art, and can be obtained by those skilled in the art through commercial channels.
[0024] When an amount, concentration or other value or parameter is expressed as a range, a preferred range or a range defined by a series of upper preferred values and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including the range "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described herein, unless otherwise stated, the range is intended to include its end values and all integers and fractions within the range. In the present specification and claims, range definitions can be combined and / or interchanged, and if not otherwise stated, these ranges include all subranges contained therein.
[0025] The carbon black used in the following examples is all nano carbon black.
[0026] Example 1
[0027] Preparation of a rubber hose for oil mining:
[0028] The raw materials calculated by weight are: 85 parts of nitrile rubber, 12 parts of flake graphite (average particle size 200 μm), 0.5 parts of carbon aerogel nanoparticles (average particle size 80 nm), 1 part of diisopropylphenol peroxide, 1 part of carbon black, and 1 part of TMQ antioxidant.
[0029] The preparation method of the carbon aerogel nanoparticles comprises:
[0030] Resorcinol and formaldehyde were mixed in a molar ratio of 1:2, and then solvent water and a small amount of sodium carbonate were added as a catalyst. After stirring, the mixture was kept warm at 30°C for 1 hour, heated to 50°C for 1 hour, and then heated to 90°C for 1 hour to obtain a hydrogel. The solvent was replaced with acetone three times, and then dried to obtain aerogel. Under a nitrogen atmosphere, the mixture was heated to 1050°C, carbonized for 4 hours, and then crushed to obtain aerogel nanoparticles.
[0031] Rubber hose preparation:
[0032] Pre-mixing the flake filler and the aerogel nanoparticles and stirring and dispersing them for 10 minutes to obtain a first mixture;
[0033] The remaining raw materials are mixed with the first mixture and added into a mixer for mixing at 140° C. for 10 minutes, and then the mixed rubber material is extruded through an extruder to obtain a rubber hose blank;
[0034] The rubber hose blank was heated to 160° C. at 0.2 MPa and vulcanized for 20 min to obtain a rubber hose.
[0035] Example 2
[0036] On the basis of Example 1, keeping other conditions unchanged, the weight parts of each raw material are: 80 parts of nitrile rubber, 10 parts of flake graphite (average particle size 200 μm), 0.1 parts of carbon aerogel nanoparticles (average particle size 80 nm), 0.2 parts of diisopropylphenol peroxide, 1 part of carbon black, and 0.3 parts of TMQ antioxidant.
[0037] Example 3
[0038] On the basis of Example 1, keeping other conditions unchanged, the weight parts of each raw material are: 90 parts of nitrile rubber, 15 parts of flake graphite (average particle size 200 μm), 1 part of carbon aerogel nanoparticles (average particle size 80 nm), 1 part of diisopropylphenol peroxide, 3 parts of carbon black, and 1 part of TMQ antioxidant.
[0039] Example 4
[0040] On the basis of Example 1, keeping other conditions unchanged, the average particle size of flake graphite is 100 μm.
[0041] Example 5
[0042] On the basis of Example 1, keeping other conditions unchanged, the average particle size of flake graphite is 1000 μm.
[0043] Example 6
[0044] On the basis of Example 1, keeping other conditions unchanged, the average particle size of the carbon aerogel nanoparticles is 50 nm.
[0045] Example 7
[0046] On the basis of Example 1, keeping other conditions unchanged, the average particle size of the carbon aerogel nanoparticles is 100 nm.
[0047] Example 8
[0048] On the basis of Example 1, keeping other conditions unchanged, the aerogel nanoparticles are pre-modified, and the modification method is: dissolving the terminal hydroxyl nitrile rubber in toluene to obtain an active solution with a mass concentration of 5%, adding carbon aerogel nanoparticles to the active solution, ultrasonically treating for 60 minutes, and then filtering and drying to obtain grafted modified aerogel nanoparticles.
[0049] Example 9
[0050] On the basis of Example 1, keeping other conditions unchanged, the aerogel nanoparticles are pre-modified, and the modification method is: dissolving the terminal hydroxyl nitrile rubber in toluene to obtain an active solution with a mass concentration of 10%, adding carbon aerogel nanoparticles to the active solution, ultrasonically treating for 30 minutes, and then filtering and drying to obtain grafted modified aerogel nanoparticles.
[0051] Example 10
[0052] On the basis of Example 1, keeping other conditions unchanged, the flake graphite was replaced by mica powder of the same size.
[0053] Embodiment 11
[0054] On the basis of Example 1, keeping other conditions unchanged, the flake graphite is replaced by mica iron oxide of the same size.
[0055] Example 12
[0056] On the basis of Example 1, other conditions were kept unchanged, and the carbon aerogel nanoparticles were replaced with silica aerogel nanoparticles of the same size.
[0057] Comparative Example 1
[0058] On the basis of Example 1, keeping other conditions unchanged, the average particle size of flake graphite is 50 μm.
[0059] Comparative Example 2
[0060] On the basis of Example 1, keeping other conditions unchanged, the average particle size of flake graphite is 1500 μm.
[0061] Comparative Example 3
[0062] On the basis of Example 1, keeping other conditions unchanged, the average particle size of the carbon aerogel nanoparticles is 20 nm.
[0063] Comparative Example 4
[0064] On the basis of Example 1, keeping other conditions unchanged, the average particle size of the carbon aerogel nanoparticles is 200 nm.
[0065] Comparative Example 5
[0066] On the basis of Example 1, other conditions were kept unchanged and the carbon aerogel nanoparticles were replaced with flake graphite.
[0067] Comparative Example 6
[0068] On the basis of Example 1, other conditions were kept unchanged and the flake graphite was replaced by carbon aerogel nanoparticles.
[0069] Comparative Example 7
[0070] On the basis of Example 8, other conditions were kept unchanged and the mass concentration of the hydroxy-terminated nitrile rubber in the active solution was adjusted to 2%.
[0071] Comparative Example 8
[0072] On the basis of Example 9, keeping other conditions unchanged, the mass concentration of the hydroxy-terminated nitrile rubber in the active solution was adjusted to 15%.
[0073] Comparative Example 9
[0074] On the basis of Example 1, other conditions were kept unchanged and flake graphite and carbon nano aerogel were replaced by carbon black.
[0075] The following performance tests were performed on the rubber hoses prepared in the above examples and comparative examples:
[0076] 1. Oil resistance test: Cut rubber hoses of the same weight (m1) into pieces and soak them in the test oil at 150°C for 24 hours. Then remove the surface residue and weigh it (m2). Calculate the expansion rate = (m2-m1) / m1*100%, and get the results shown in the following table:
[0077]
[0078] It is not difficult to see that when the rubber hose is prepared using the formula of the present invention, the resulting rubber material has good tolerance to the test oil, and the expansion rate is greatly reduced in a high temperature and high oil environment for a long time.
[0079] At the same time, the wear resistance of the rubber hoses prepared in the above embodiments and comparative examples was tested by placing rubber hose slices of the same size and mass on the wear test platform for 300 tests, and calculating the weight loss after wear, and calculating the wear rate = wear amount / original weight*100%, and obtaining the following table results:
[0080]
[0081] It can be seen from the data in the above table that the rubber hose prepared by the present invention not only has greatly improved oil resistance, but also has greatly improved wear resistance.
[0082] At the same time, the rubber hoses prepared in the above embodiments and comparative examples were subjected to a 4000h salt spray resistance test, and the tested rubber hoses were tested for oil resistance again, and compared with the oil resistance test in the initial state, and the reduction rate of oil resistance was compared, the reduction rate = (swelling rate after 4000h salt spray - initial swelling rate) / initial swelling rate * 100%, and the results shown in the following table were obtained after calculation:
[0083]
[0084] It is not difficult to see that the rubber hose prepared by the present application scheme also exhibits good aging resistance, especially after salt spray corrosion, the flake filler and aerogel nanoparticles form a good aging resistance effect.
[0085] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A rubber hose for oil mining, characterized in that: The raw materials of the rubber hose include, by weight: 80-90 parts of base rubber, 10-15 parts of flake filler, 0.1-1 part of aerogel nanoparticles and 1-5 parts of additives. The average particle size of the flake filler is 100-1000 μm, the average particle size of the aerogel nanoparticles is 50-100 nm, the flake filler is flake graphite, and the aerogel nanoparticles are carbon aerogel nanoparticles.
2. The rubber hose for oil mining as claimed in claim 1, characterized in that: The surface of the aerogel nanoparticles is subjected to graft modification treatment with terminal hydroxyl nitrile rubber, and the modification method comprises: dissolving the terminal hydroxyl nitrile rubber in toluene to obtain an active solution, adding the aerogel nanoparticles into the active solution, ultrasonically treating for 30-60 minutes, filtering and drying to obtain the graft modified aerogel nanoparticles.
3. The rubber hose for oil mining as claimed in claim 2, characterized in that: The mass concentration of the hydroxy-terminated nitrile rubber in the active solution is 5-10%.
4. The rubber hose for oil mining as claimed in claim 1, characterized in that: The base rubber is one of nitrile rubber, styrene butadiene rubber, chloroprene rubber and fluororubber.
5. The rubber hose for oil mining as claimed in claim 1, characterized in that: The auxiliary agents include fillers, vulcanizing agents and anti-aging agents.
6. A method for preparing a rubber hose for oil mining as claimed in any one of claims 1 to 5, characterized in that: The steps include: Step 1: firstly, mixing and dispersing the flake filler and the aerogel nanoparticles to obtain a first mixture; Step 2: Mix the remaining raw materials with the first mixture and add them into a mixer for mixing, and extrude the mixed materials through an extruder to obtain a rubber hose; Step 3: vulcanize the rubber hose to obtain a rubber hose.
Citation Information
Patent Citations
Preparation of wear resistant rubber composite material
CN101463149A
Aging-resistant inner-layer rubber for high-pressure hose
CN109400987A
Fluororubber modified carbon aerogel and preparation method thereof
CN113617301A
Oil-resistant and wear-resistant cable material for oil platform and preparation method of oil-resistant and wear-resistant cable material
CN115160665A
Modified silica aerogels and silicone rubbers containing the same
GB805102A
